Iatrogenic Cushing’s syndrome induced by topical steroid abuse in a patient with psoriasis: a case report - Chen, Jianwei; Sun, Jiawei; Wang, Chunnuo; Zhao, Haiying; Li, Wei; Wang, Shujun; Du, Sina (Frontiers in Medicine, 2025)
BackgroundIatrogenic Cushing’s syndrome (ICS) is frequently observed as a side effect of long-term steroid treatment. While it is most commonly linked to the administration of oral steroids, rare instances have been reported following the inadvertent use of topical steroids, which can lead to severe clinical consequences.Case summaryThis case report details the case of a psoriasis patient who exhibited Cushing-like symptoms, such as central obesity, violaceous striae, moon face, and hypertension, following the long-term use of a so-called “herbal cream” containing clobetasol propionate. Laboratory investigations revealed hypokalemia, a disrupted cortisol circadian rhythm, and suppressed plasma ACTH levels. Additionally, bone mineral density analysis indicated a reduction in bone density.ConclusionThis case underscores the critical need for clinicians to remain vigilant about the potential systemic adverse effects of topical glucocorticoids, particularly in psoriasis patients, where even minimal concentrations of clobetasol propionate can precipitate ICS. Furthermore, identifying the source of exogenous glucocorticoids in ICS necessitates a thorough review of the patient’s medication history, encompassing over-the-counter drugs and supplements. It is important that medication use be guided by specialist consultation and rigorous monitoring, rather than unsupervised self-medication.